2021
DOI: 10.1080/00036846.2021.1966370
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fiscal policy on non-oil GDP in Saudi Arabia

Abstract: This paper examined the impact of fiscal policy on non-oil GDP in Saudi Arabia, the world's largest oil exporter, over the annual period 1989-2018. We employed various cointegration methods within the framework of the augmented production function and estimated that government current and capital expenditure, in addition to non-oil labour and capital, have statistically significant positive effects on non-oil GDP. We tested whether the recent oil price decline and the implemented economic reforms caused a brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
(54 reference statements)
2
3
0
Order By: Relevance
“…Tis indicates that variables have a positive impact on nonoil economic growth. Our fndings support most studies that found a considerably favorable efect of fnancial innovation on nonoil economic growth in Saudi Arabia [31,82,83,87]. Tus, fnancial innovation promotes nonoil economic development by hastening the accumulation of capital, facilitating fnancial intermediation, and improving payment methods.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Tis indicates that variables have a positive impact on nonoil economic growth. Our fndings support most studies that found a considerably favorable efect of fnancial innovation on nonoil economic growth in Saudi Arabia [31,82,83,87]. Tus, fnancial innovation promotes nonoil economic development by hastening the accumulation of capital, facilitating fnancial intermediation, and improving payment methods.…”
supporting
confidence: 86%
“…Tus, fnancial innovation promotes nonoil economic development by hastening the accumulation of capital, facilitating fnancial intermediation, and improving payment methods. Moreover, the fndings of this paper are similar to most empirical studies that found that the non-oil trade has a signifcant efect on the economic growth and GDP [87,88]. Tus, nonoil trade openness promotes nonoil economic development by importing new technology, ideas, and information in addition to buying and selling products and services.…”
supporting
confidence: 78%
“…Several references have discussed this policy update, Hasanov et al (2022) and Brini and Jemmali (2016).…”
Section: Policies' Strength and The Efficiency Of Government Spendingmentioning
confidence: 99%
“…Second, a large portion of Saudi Arabia's government revenues come from oil exports (see, e.g., [113,116]). Government consumption, again regardless of how it is measured, has a considerable positive effect on the Saudi CPI, which is the numerator in the REER formula, as described in the Data section.…”
Section: Appendix B Conceptual Framework For Modeling the Saudi Reermentioning
confidence: 99%